Christology of Tuak-Tempayan: Christological Endeavors in the Land of Western Borneo - Budi, Fransiskus Nong (Studia Philosophica et Theologica, 2024)
This paper presents Christological research conducted in Nanga Mahap (Sekadau, West Kalimantan). The main focus of this study is on the phenomenon of Tuak Tempayan, a significant cultural reality considered to hold a wealth of values with open possibilities for Christological interpretation for the teaching of faith. Tuak Tempayan can be a means ofCatechesis in explaining the reality of Jesus Christ who has divine and human nature, God and Man. The research was carried out using a new methodology called Phenomenological Research. This method is a phenomenological approach applied to the pure experience of an encounter within a culture and then validated through research to arrive at its original meaning. The results are then interpreted dialogically with Christology to arrive at a new meaning for catechesis and the transformation of faith life. Such an effort is nothing but doing Christology from the context, an attempt to understand Jesus Christ through localities and local contexts.